2020
DOI: 10.3390/app10176070
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Plasmid DNA Delivery and Cell Viability Dynamics for Optimal Cell Electrotransfection In Vitro

Abstract: Electroporation is an effective method for delivering plasmid DNA molecules into cells. The efficiency of gene electrotransfer depends on several factors. To achieve high transfection efficiency while maintaining cell viability is a tedious task in electroporation. Here, we present a combined study in which the dynamics of both evaluation types of transfection efficiency and the cell viability were evaluated in dependence of plasmid concentration as well as at the different number of high voltage (HV) electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Higher concentrations of pDNA require a higher amount of PEI for modi cation and permeabilization of endosomal membrane, which causes a higher cytotoxic effect of polyplexes on cell viability [42,43]. In addition, regardless of PEI dosage, an excess of pDNA itself can also contribute to cellular toxicity [44,45]. There are pieces of evidence showing that regardless of the transfection method, the concentration of nucleic acid is also critical for enhancing e ciency and minimizing toxicity [44,46].…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of pDNA require a higher amount of PEI for modi cation and permeabilization of endosomal membrane, which causes a higher cytotoxic effect of polyplexes on cell viability [42,43]. In addition, regardless of PEI dosage, an excess of pDNA itself can also contribute to cellular toxicity [44,45]. There are pieces of evidence showing that regardless of the transfection method, the concentration of nucleic acid is also critical for enhancing e ciency and minimizing toxicity [44,46].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of fetal bovine serum was shown to yield better transduction efficiency than bovine calf serum during transduction (Denning et al, 2013). (Haas et al, 2000;Ikeda et al, 2002;Denning et al, 2013) Potter & Heller, 2003;Molnar et al, 2004;Yao et al, 2009;Hornstein et al, 2016;Chopra et al, 2020;Sherba et al, 2020) (Stevenson et al, 2006;Terakawa et al, 2006;Tsen et al, 2009) (Wells et al, 1998;Dahlhoff et al, 2012;Mellott, Forrest & Detamore, 2013;Chow et al, 2016) (Ogawa, Tachibana & Kondo, 2006;Kinoshita & Hynynen, 2007;Zhou et al, 2012) (Mykhaylyk et al, 2007;Fouriki et al, 2010;Kardos & Rabussay, 2012;Wang et al, 2014) Likewise, polycations such as DEAE-dextran were shown to minimize repulsion forces between negatively-charged cells and facilitated viral transduction (Denning et al, 2013).…”
Section: Factors Influencing the Efficiency Of Viral Transfectionmentioning
confidence: 99%
“…Prolonged electroporation with high voltage applied could potentially lead to cell damage and reduce transfection efficiency (Molnar et al, 2004). The electro-transfection efficiency can also be improved by increasing the number of electric pulses, but this may reduce the cell viability (Chopra et al, 2020). On the other side, the electro-transfection efficiency is dependent on the type of cell used and the electroporation condition should be optimized whenever a new cell type is going to be electro-transfected (Potter & Heller, 2003).…”
Section: Factors Influencing Efficiency Of Physical/mechanical Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged electroporation with high voltage applied could potentially lead to cell damage and reduce transfection efficiency (Molnar et al 2004). The electro-transfection efficiency can also be improved by increasing the number of electric pulses, but this may reduce the cell viability (Chopra et al 2020). On the other side, the electro-transfection efficiency is dependent on the type of cell used and the electroporation condition should be optimized whenever a new cell type is going to be electro-transfected (Potter and Heller 2003).…”
Section: Factors Influencing Efficiency Of Physical/mechanical Transf...mentioning
confidence: 99%